Quantitative and physical evaluation of patchouli essential oils obtained from different sources 0f pogostemon cablin - Hussin, Norma; Mondello, Luigi; Costa, Rosaria; Dugo, Paola; Nik Yusoff, Nik Mohd. Idris; Yarmo, Mohd Ambar; Ab Wahab, Ahmad; Said, Mamot (Natural Product Inc., 2012)
Patchouli essential oil can be obtained from fresh, dried and fermented plant material. It is a highly valuable product in the fragrance industry and its quality changes depending upon raw material age and oil storage. In this work, patchouli essential oils derived from different treatments have been subjected to GCFID quantitative analysis using an internal standard (ISTD) method with response factors (RF). Samples were obtained from i) fresh plants; ii) hydrodistillation of one year mature and fermented plants; iii) hydrodistillation of one year mature plants; iv) commercial products from Indonesia and Malaysia. Linear Retention Indices (LRI) for both polar and non-polar GC-MS analyses were also measured as a tool for qualitative analysis towards a homologous series of C7- C30 n-alkanes. The results obtained confirmed that, in all samples, patchouli alcohol was the main volatile constituent, with higher amount in lab-scale produced oils, compared with commercial samples. Other major compounds, in lab oils and commercial samples respectively, were: δ-guaiene, α-guaiene, pogostol, seychellene and α-patchoulene. Another 36 compounds were also found.